Auxins and Cytokinins elicit a differentiated response in the formation of shoots and roots in Cattleya maxima Lindl and Phalaenopsis amabilis (L) Blume - Saravia-Castillo, Gabriela (2022)
Orchids have a long period of production and need to be under the right conditions. Therefore, in vitro propagation is an alternative to reduce production time. This study aimed to determine the optimal in vitro propagation conditions in two species of orchids, Cattleya maxima Lindl. and Phalaenopsis amabilis (L.) Blume. For this goal, two experiments were carried out: multiplication and rooting, for both species. In the multiplication experiment, the treatments were differentiated according to the complement of MS (Murashige and Skoog medium), banana flour, kinetin or 6-Benzylaminopurine (BAP). Meanwhile, in the rooting experiment, the complements were banana flour, Indol-3-butiric acid (IBA), Naphthaleneacetic acid (NAA) or 2,4-Dichlorophenoxyacetic acid (2,4-D). According to the results, banana flour (50 g.L-1) increased the plantlet height in C. maxima (multiplication) and P. amabilis (rooting). Kinetin (0.003 g.L-1) and BAP (0.005 g.L-1) increased the number of shoots and leaves in C. maxima, in multiplication experiment. In rooting experiment, NAA (0.003 g.L-1) increased significantly the number of leaves in C. maxima. The root formation was notably stimulated by banana flour in both species. Likewise, 2,4-D (0.003 g.L-1) can cause phytotoxic effects and inhibit root formation. In conclusion, C. maxima was more robust than P. amabilis since in all studied variables the former presented the highest values. Furthermore, C. maxima responds adequately to application of kinetin and BAP to increase the aerial part of the plant, however, they inhibit the root formation. In contrast, kinetin and BAP do not limit root growth in P. amabilis.